Q. rotundifolia and P. hybrida pollen extracts induced basophil degranulation: study using a cell line expressing human FcERI. - Antunes, Célia (2017)
Nowadays skin prick tests remain the favourite methodology in allergy diagnosis to aeroallergens. These tests, however, cause discomfort to the patient. Several biochemical methods are available but have limited diagnostic power as biological response, hence allergic reaction, is not predicted by these tests. A biological assay allowing the evaluation of allergic response to allergens is lacking. The aim of this work was to investigate the value of a rat basophil cell line expressing human high affinity IgE receptor (FcERI) for the evaluation of specific response to allergens. FACS analysis was used to determine FcERI expression (APC-A). Pollen extracts from different species were prepared with ammonium bicarbonate buffer, lyophilized and stored at -80ºC until use. Batches of RBL-h21 cells were sensitized with selected pools of human sera (purified IgE was used as control) and were stimulated with pollen extracts or Anti-IgE antibody. Histamine release (% degranulation) was determined a ß-hesoaminidase (tracer) assay. Batches of RBL-h21 cells sensitized (human sera) to grasses (D. glomerata), olive, oak or plane exhibited selective and dose-dependent degranulation upon selective stimulation with pollen extracts in the range of 1-200μg/mL. Maximal degranulation (>25%) was observed for 50, 120 and 62μg/mL for grass, oak and plane, respectively, while the lowest concentration with observed effect was 12μg/mL for any of the extracts. The results show that RBL-h21 cells sensitized with human sera exhibit specific and dose-dependent degranulation upon stimulation with pollen extract containing allergens suggesting this bioassay may constitute a useful tool to evaluate allergic responses both for research and/or diagnostics.